Higher education is associated with a better rheumatoid arthritis outcome concerning for pain and function but not disease activity: results from the EIRA cohort and Swedish rheumatology register - Jiang, Xia (Arthritis Res Ther, 2015)
INTRODUCTION: Whether low socioeconomic status (SES) is associated with worse rheumatoid arthritis (RA) outcomes in countries with general tax-financed healthcare systems (such as Sweden) remains to be elucidated. Our aim was to investigate the influence of educational background (achieving university/college degree (high) or not (low)) on the outcomes of early RA, in terms of disease activity (DAS28), pain (VAS-pain), and functional impairment (HAQ). METHODS: We evaluated DMARD-naïve RA patients recruited in the Epidemiological Investigation of RA (EIRA) study with outcomes followed in the Swedish Rheumatology Quality (SRQ) register (N = 3021). Outcomes were categorized in three ways: 1) scores equal to/above median vs. below median; 2) DAS28-based low disease activity, good response, remission; 3) scores decreased over the median vs. less than median. Associations between educational background and outcomes were calculated by modified Poisson regressions, at diagnosis and at each of the three standard (3, 6, 12 months) follow-up visits. RESULTS: Patients with different educational background had similar symptom durations (195 days) and anti-rheumatic therapies at baseline, and comparable treatment patterns during follow-up. Patients with a high education level had significantly less pain and less functional disability at baseline and throughout the whole follow-up period (VAS-pain: baseline: 49 (28-67) vs. 53 (33-71), p <0.0001; 1-year visit: RR = 0.81 (95 % CI 0.73-0.90). HAQ: baseline: 0.88 (0.50-1.38) vs. 1.00 (0.63-1.50), p = 0.001; 1-year visit: 0.84 (0.77-0.92)). They also had greater chances to achieve pain remission (VAS-pain ≤20) after one year (1.17 (1.07-1.28)). Adjustments for smoking and BMI altered the results only marginally. Educational background did not influence DAS28-based outcomes. CONCLUSION: In Sweden, with tax-financed, generally accessible healthcare system, RA patients with a high education level experienced less pain and less functional disability. Further, these patients achieved pain remission more often during the first year receiving standard care. Importantly, education background affected neither time to referral to rheumatologists, disease activity nor anti-rheumatic treatments.